Isolation of Alcohol Dehydrogenase cDNA and Basal Regulatory Region from Metroxylon sagu - Hairul Azman, Roslan; Ching, Ching Wee (Hindawi Pub. Corp., 2012)
Alcohol dehydrogenase (Adh) is a versatile enzyme involved in many biochemical pathways in plants such as in germination and stress tolerance. Sago palm is plant with much importance to the state of Sarawak as one of the most important crops that bring revenue with the advantage of being able to withstand various biotic and abiotic stresses such as heat, pathogens, and water logging. Here we report the isolation of sago palm Adh cDNA and its putative promoter region via the use of rapid amplification of cDNA ends (RACE) and genomic walking. The isolated cDNA was characterized and determined to be 1464 bp long encoding for 380 amino acids. BLAST analysis showed that the Adh is similar to the Adh1 group with 91% and 85% homology with Elaeis guineensis and Washingtonia robusta, respectively. The putative basal msAdh1 regulatory region was further determined to contain promoter signals of TATA and AGGA boxes and predicted amino acids analyses showed several Adh-specific motifs such as the two zincbinding domains that bind to the adenosine ribose of the coenzyme and binding to alcohol substrate. A phylogenetic tree was also constructed using the predicted amino acid showed clear separation of Adh from bacteria and clustered within the plant Adh group.